2017
DOI: 10.1017/s0007485317000955
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition preferences of dengue vectors;Aedes aegyptiandAedes albopictusin Sri Lanka under laboratory settings

Abstract: Investigations on oviposition behaviour of dengue vectors are critical for effective controlling of vector breeding. Therefore, the aim of the present study was to determine the oviposition behaviour of dengue vectors, Aedes aegypti and Aedes albopictus in Sri Lanka. Batches of 1000 adult mosquitoes (1 : 1, male: female ratio) housed in rearing cages were used for each experimental setup from Ae. aegypti and Ae. albopictus. Oviposition responses with respect to the size of the ovitrap, colours of the ovitrap, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…We speculated in this study mosquitoes' oviposition behavior is mainly in uenced by vision. Studies have shown that yellow is more attractive to Culex pipiens pallens for laying eggs than white [39], which in this experiment after coagulation-occulation, yellow alum oc deposited at the bottom of the ovitrap, which is considered to be nutrient-rich for larvae growing, therefore more female Culex pipiens pallens mosquitoes preferred O1 as breeding sites [40].…”
Section: Table 1 Results Of Two Replications In Mosquito Oviposition mentioning
confidence: 70%
See 1 more Smart Citation
“…We speculated in this study mosquitoes' oviposition behavior is mainly in uenced by vision. Studies have shown that yellow is more attractive to Culex pipiens pallens for laying eggs than white [39], which in this experiment after coagulation-occulation, yellow alum oc deposited at the bottom of the ovitrap, which is considered to be nutrient-rich for larvae growing, therefore more female Culex pipiens pallens mosquitoes preferred O1 as breeding sites [40].…”
Section: Table 1 Results Of Two Replications In Mosquito Oviposition mentioning
confidence: 70%
“…Though in laboratory, coagulant PACl could promote oviposition preference of female Culex pipiens pallens to some extent, however, considering the limitation of laboratory, and actually female Culex pipiens pallens prefer ovitrap in deep color as breeding sites [39], PACl may avoid mosquitoes' oviposition if used out-doors. Still, coagulant modi cation may help to solve.…”
Section: Discussionmentioning
confidence: 99%
“…Collected eggs were transferred to 1 L plastic trays with deoxygenated water in the Arthropod Containment Facility at the MMU and kept for 8 hours (hrs) for hatching. Hatched larvae were counted and transferred into properly labeled plastic trays (40 cm x 30 cm x 5 cm) containing 2 L of distilled water [16]. For the purpose of quality control and maintenance of uniform size of the larvae; a density of 1 000 larvae per tray was maintained.…”
Section: Methodsmentioning
confidence: 99%
“…Sugar solutions were replaced every two days to avoid any fungal growth inside the cage. Mosquitoes were reared in an environment with a temperature of 26-27 o C and 78-80% RH under 12 hrs light and 12 hrs dark cycle [16].…”
Section: Rearing Of the Adult Ae Aegyptimentioning
confidence: 99%
See 1 more Smart Citation